(untitled) (Advances in Systems Science and Applications, 2022)
The paper is devoted to a method for constructing exact solutions of evolutionary differential equations with two space variables.The method uses the theory of symmetries of completely integrable distributions. As an example, we consider a linear parabolic equation that arises in filtration theory, thermodynamics, and mathematical biology. Dynamics are calculated for this equation and classes of their exact solutions are constructed.